157k views
3 votes
Negative solution for Multi-step equations

Negative solution for Multi-step equations-example-1
User PomfCaster
by
4.4k points

1 Answer

3 votes

Answer:


(1)/(2)(4x+6)+3x=7x+9


(1)/(2)(4x+8)+3x=7x+9

Explanation:

By putting the numbers in the given equation,


(1)/(2)(4x+6)+3x=7x+9

2x + 3 + 3x = 7x + 9

5x + 3 = 7x + 9

(5x + 3) - 7x = (7x + 9) - 7x

(5x - 7x) + 3 = 9

-2x + 3 = 9

(-2x + 3) - 3 = 9 - 3

-2x = 6


-(2x)/(2)=(6)/(2)

-x = 3

x = -3

Therefore, our equation is correct which has a negative result.

In place of 6 if we use 8, value of x will be negative again.

User Eric Goncalves
by
5.4k points